Models of hemispheric specialization mechanisms - Kočiūnas , R. (Psichologija, 1980)
In this article the main models of functional asymmetry mechanisms are reviewed: the model of cerebral dominance, of post-exposural directional scanning, of attention, of cognitive strategy and of memory. These models include different aspects of hemispheric dominance. A more detailed explanation of functional asymmetry mechanisms will be possible only having evaluated the importance of all the main factors, such as attention, the strategy of information processing, memory, and others.